Analysis of the Distribution of Zakat, Infaq and Alms at the Baznas Tangerang City During the Covid-19 Pandemic - Khumaini, Sabik; Nurzansyah, M.; Has, Fadlie (ITQAN: Journal of Islamic Economics, Management, and Finance, 2022)
Zakat is one of the characteristics of the Islamic economic system. It is one of the most effective instruments to improve the welfare of the ummah and alleviate poverty. This study aims to determine the distribution mechanism of zakat, infaq and alms in Baznas Tangerang City and to determine the role of zakat, infaq and alms distribution for the worthies during the covid 19 pandemic. This study uses a qualitative approach using primary and secondary data. The results showed that the zakat distribution mechanism that is carried out by BAZNAS Tangerang City used two supporting activities, namely: productive assistance and consumptive assistance. In order to get the assistance, the worthies can come directly to BAZNAS Tangerang city either through individuals, institutions, or organizations. The distribution of zakat is carried out by BAZNAS Tangerang City through zakat, infaq, and alms funds by carrying out several activities which have a role in helping the worthies who are affected by the COVID-19 pandemic. It is also a solution for the worthies who are in difficult situations and zakat is used as a source of assistance in dealing with the impact of covid 19.